Spit guards, ethical policing and the need for an evidence-based approach. Issue 3 (9th July 2018) - Joyce, Peter; Laverick, Wendy
Abstract : Purpose: The purpose of this paper is to assess the advantages and disadvantages of the use of spit guards by police forces in the UK and to make recommendations regarding an evidence-based approach to decisions related to the use of such equipment. Design/methodology/approach: The paper is based upon an examination of a range of primary source material, secondary sources and grey literature. Findings: Although the use of spit guards can be justified by factors that include the need to protect police officers from contracting serious infectious diseases, there are a number of problems that concern ethical policing and human rights. Concerns arise when spit guards are deployed against vulnerable individuals, are used offensively rather than defensively and when such equipment is deployed disproportionately against persons from Black and Minority Ethnic (BME) communities. Additionally, the image of the police may suffer if spit guards are accompanied by the use of excessive force which may be perceived as an abuse of police power. Practical implications: The paper makes recommendations that a comprehensive evidence base is required to assist practitioners to make informed decisions regarding the deployment of spit guards. This evidence base should include the extent to which officers are spat at, medical evidence relating to spitting and the transmission of serious diseases, the views of the public concerning the deployment of spit guards and estimations as to whether such equipment will deter spitting by suspects of crime. Originality/value: This paper provides an original academic contribution to the ongoing debate on the use of spit guards within policing. In particular, it brings together a wide range of material that relates to this topic and presents it as a coherent set of arguments located in a single source.